Carbon Material Based Electrochemical Immunosensor for Gastric Cancer Markers Detection - Zhang, Zhuliang; Peng, Minsi; Li, Defeng; Yao, Jun; Li, Yingxue; Wu, Benhua; Wang, Lisheng; Xu, Zhenglei (Frontiers in Chemistry, 2021)
Gastric cancer is one of the most common malignant tumors, and early diagnosis will be of great significance to improve the survival quality and overall treatment outcome evaluation of patients. Nanoelectrochemical immunosensor is an emerging biosensor combining nanotechnology, electrochemical analysis method and immunological technology, which has simple operation, fast analysis speed, high sensitivity and good selectivity. This mini-review summarized immunoassay techniques, nanotechnology and electrochemical sensing for the early detection of gastric cancer. In particular, we focus on the tension of carbon nanomaterials in this field, including the functionalized preparation of materials, signal enhancement and the construction of novel sensing interfaces. Currently, various tumor markers are being developed, but the more recognized gastric cancer tumor markers are carcinoembryonic antigen (CEA), carbohydrate antigen (CA), CD44V9, miRNAs and programmed death ligand 1. Among them, the electrochemical immunosensor allows the detection of CEA, CA and miRNAs. The mini-review focused on the development of using carbon based materials, especially carbon nanotubes and graphene for immunosensor fabrication and gastric cancer markers detection.